2015
DOI: 10.1088/2051-672x/3/1/014003
|View full text |Cite
|
Sign up to set email alerts
|

The influence of heat accumulation on the surface roughness in powder-bed additive manufacturing

Abstract: The influence of heat accumulation on surface roughness during powder-bed additive manufacturing was investigated. A series of Ti-6Al-4V thin plates were produced by using an identical heat input by electron beam melting® (EBM). Spacing distances of 5 mm, 10 mm, and 20 mm were used. The surface roughness of as-built thin plates was measured using a two-axis profilometer. A numerical model was developed to study the influence of spacing distance on heat accumulation. An inverse relationship between the spacing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(55 citation statements)
references
References 17 publications
0
53
0
2
Order By: Relevance
“…Bacchewar et al [34] identified laser power as especially influential in the surface roughness of downward facing surfaces; for upward facing surfaces, the laser power had minimal impact on surface roughness. Jamshidinia and Kovacevic [35] found that the proximity of parts during the build process affects the heat accumulation in the part and therefore influences its surface roughness. In Stimpson et al [36], they expanded upon their initial study in [30] develop a correlation to estimate friction factor given the parts' mean relative roughness, which the authors calculated from SEM images.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bacchewar et al [34] identified laser power as especially influential in the surface roughness of downward facing surfaces; for upward facing surfaces, the laser power had minimal impact on surface roughness. Jamshidinia and Kovacevic [35] found that the proximity of parts during the build process affects the heat accumulation in the part and therefore influences its surface roughness. In Stimpson et al [36], they expanded upon their initial study in [30] develop a correlation to estimate friction factor given the parts' mean relative roughness, which the authors calculated from SEM images.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The interaction between the high-energy laser typical of LPBF equipment and the metal powder bed can result in powder contamination through different phenomena including agglomeration, partial fusing, partial/full oxidation, metal vapor condensate, and generation of spatter [32][33][34][35][36][37][38][39][40]. These phenomena can alter not only the properties of the reused powder (i.e., flowability, chemical composition, tap density, particle size), but also the surface (i.e., roughness), microstructural (i.e., local variation of chemical composition, pore formation), and mechanical properties of the final part.…”
Section: Introductionmentioning
confidence: 99%
“…ing a part with a highly rough surface during the AM by powder bed technologies. Jamshidinia and Kovacevic (2015) studied the influence of heat accumulation on the surface roughness of Ti-6Al-4 V produced by EBM®. The experimental and numerical results showed that the surface quality of buildups could be affected not only by process parameters, but also by the arrangement of components in the buildup chamber.…”
Section: Comparison Of the Experimental And Numerical Resultsmentioning
confidence: 99%